THU0375 ASDAS-Based Remission Was Less Frequent than BASDAI-Based Remission, and Both Were Related To CRP and Smoking in Early Axial Spondyloarthritis. The Desir Cohort. (15th July 2016) - Wendling, D.; Guillot, X.; Gossec, L.; Prati, C.; Saraux, A.; Dougados, M.
Abstract : Background: Remission is the final goal for treat to target strategy in axial spondyloarthritis (axSpA). No clear definition is currently recognized, but ASDAS-CRP inactive state or BASDAI threshold (1) have been proposed. The frequency of remission using these definitions and factors associated with remission are unknown in early axSpA. Objectives: To evaluate the percentage of patients in remission in early AxSpA, comparing different definitions of remission, and to evaluate factors associated with remission at inclusion in the DESIR cohort and after 24 months. Methods: DESIR is a prospective observational cohort of patients with recent onset (less than 3 years) inflammatory back pain, beginning before 45 years, suggestive of axial SpA. For each of three definitions of remission (ASAS partial remission (PR), ASDAS-CRP less than 1.3 (ASDAS-R), BASDAI less than 3.6 (1) (BASDAI-R)), the ability to detect patients in remission according to the two other definitions was assessed using ROC curves and Areas Under the Curve (AUC). Data at baseline (M0) and M24 were analyzed, to look for factors (clinical, biological and imaging) associated with remission in uni and multivariate analysis by logistic regression. Results: 706 patients were evaluated at M0 and 577 at M24. At M0, the percentage of patients in remission was 4% (PR), 8% (ASDAS) 34% (BASDAI), and at M24: 15%, 24% and 54% respectively, in the whole population and in Amor, ESSG and ASAS classified patients, but lower in mNY patients (data not shown). BASDAI less than 3.6 detected best patients in PR and ASDAS-R, with AUC of 0.84 and 0.86 respectively. In univariate analysis at M0, lower ESR and CRP, DKK-1, low BMI, male gender, absence of psoriasis, less smoking, HLA-B27 positivity, ASAS criteria fulfillment, positive sacro iliac imaging, less analgesics use and less subsequent use of anti TNF at M24 were associated with remission (ASDAS-R, BASDAI-R). No association was found with age, disease duration, enthesitis, uveitis, IBD, NSAID use, mSASSS. In multivariate analysis, remission was associated with lower ESR, less smoking, use of analgesics. At M24, low ESR and CRP, female gender, less smoking, less NSAID use, lower NSAID score, ASAS criteria fulfillment, lower biologics use and lower systemic steroid use were associated with remission in univariate analysis. In multivariate analysis, remission was associated with less smoking, less analgesics, ASAS clinical arm fulfillment, less NSAIDs (ASDAS-R), low CRP (ASDAS-R), low BMI (BASDAI-R) (Table 1 ). Conclusions: In this population suggestive of early SpA, acute phase reactants and analgesics were associated with remission at baseline and M24, but smoking appears as a major marker of disease activity and remission in early AxSpA. References: Godfrin-Valnet M, Puyraveau M, Wendling D. J Rheumatol. 2014;41(3):617–8. Acknowledgement: The DESIR cohort is supported by an unrestricted grant from PFIZER France. Disclosure of Interest: None declared